The uncertainty of economic policies in the United States and its impact on the stock markets of some African countries: An empirical study with VAR modeling - Mosbah Lafi,; Hafidha Chammem, (Technium Social Sciences Journal, 2024)
The economic and financial integration that has taken place over the last 20 years has led to a situation where the reaction of financial markets is no longer solely due to local factors, but also to macroeconomic and financial news of regional and international origin. In this regard, we focus on the effect of the international transmission of uncertainty shocks on global stock market performance. Given that the United States is the world’s leading economic power, some studies have highlighted the adverse effects of the international propagation of US uncertainty shocks on international stock markets (Ehrmann and Fratzscher, 2009; Klobner and Sekkel, 2014; Hammoudeh et al., 2016). Using VAR modeling, our study examines the specific impact of economic policy uncertainty in the USA on the stock markets of four African countries: Tunisia, Egypt, Morocco, and South Africa. Although geographically distant from the USA, these economies are closely integrated into the global economy and are likely to be affected by international economic and political developments, particularly those originating in the USA, a major economy and a key player on the global stage.